Curriculum Development, Islamic Religious Education, Islamic Elementary School AL Azhar - Hilman Maas, Piki (Atthulab: Islamic Religion Teaching and Learning Journal, 2019)
The Islamic Education curriculum is one of the important components to create a generation of morality and martyrs. But the Islamic Religious Education curriculum has been considered only to educate cognitive aspects (transfer of knowladge) and has not touched many affective and psychomotor aspects (transfer of value). This is evident from the many students who have not been able to apply knowledge about their religion such as not performing worship well, speaking harshly and disrespectfully, disrespecting parents and teachers and a group of students who are often in shopping centers and crowds. Therefore, it is necessary to develop an Islamic Education curriculum that accommodates cognitive, affective and psychomotor aspects, so that education is not only a transfer of knowladge but also a transfer of value. Islamic Education curriculum development in this study contains the understanding of the expansion or improvement of the subject matter of the Islamic Religious Education curriculum and what is experienced by students or all efforts (engineering) programmed by Al Islam Azhar 36 Bandung in helping develop the potential of students through learning experience the potential to achieve the vision, mission, school goals. Â